Comparison of post surgical complication of urethrocutaneous fistula for distal hypospadias repair between Snodgrass and Aivar bracka Surgical Techniques - Amjad ali, Qazi; Ahmad, Shahzad; Khan, Nasir Hayat; Khan, Imran Muhammad (Khyber Journal of Medical Sciences, 2021)
Objective: Comparison of the frequency of post-surgical complication of urethrocutaneous fistula for distal penile hypospadias between Snodgrass and Aivar Bracka surgical techniques. Methods: Burn and trauma center, HMC was the place for study. The duration of study was one year, from 01/01/2020 to 31/12/2020. The study design was Randomized Controlled Trial, in which a total of 70 (35 in each group) patients were selected. The patients were divided randomly in group A and B using envelope sampling technique. Group A were assigned to Snodgrass repair technique and group B were assigned to Aivar Bracka, repair technique. Consultant plastic surgeons performed all the procedures. Both groups were followed for six months for development of urethrocutaneous fistula. Results were stratified for each procedure. Results presented in the form of tables. Results: In this study for Snodgrass hypospadias repair procedure, the mean age was 6 years ± 3.26 while for Aiver Bracka surgical procedure the mean age was 6 years ±3.41. the frequency of urethrocutaneous fistula was 9% (n=3) in Snodgrass surgical technique, where as 18% (n=6) in Aiver Bracka Surgical Technique. The frequency of urethrocutaneous fistula was significantly low in group A (p=0.2840). Conclusion: Our study concludes that Snodgrass surgical technique has less frequency of developing urethrocutaneous fistula than Aivar Bracka surgical technique for correction of distal penile hypospadias.